(untitled) (Journal of the College of Basic Education, 2025)
The present research aims to identifying Obstacles of Teaching Mathematical Problems in the Primary Stage from the Point of View of Mathematics Teachers and Supervisors, to achieve the aim the researcher has adopted The descriptive survey method approach, sample of the research includes (92) Teachers and Supervisors of Mathematics, whereby (9( supervisors and )83( teachers in the primary schools which follow the general education directory of Baghdad / al – rusafa 3 for the academic year (2023-2024), the researcher has adopted a questionnaire consist of (42) Obstacles, the sincerity and firmness was verified, and to find out the degree of impact of those Obstacles in Teaching Mathematical Problems, the researcher used statistical bag of social Sciences (SPSS) Averages and standard deviations, The results showed the included Obstacles affect the teaching of Mathematical Problems to a high degree with a general mean effect of (4.12). In the light of the results, the researcher has concluded some conclusion and also has suggested and recommended many items.